Glacial debris flows in Zailiysky Alatau over the past 120 years - A. P. Medeu; V. P. Blagovechshenskiy; N. E. Kasatkin; V. P. Kapitsa; M. K. Kasenov; Zh. T. Raymbekova (Лëд и снег, 2020)
Zailiyskiy Alatau is the most mudflow hazardous mountain region of the Republic of Kazakhstan. At the same time, this area is one of the most densely populated and economically developed one, so mudflows here cause the great damage. The paper presents results of our analysis of the glacial mudflow activity for the period from 1900 to 2019. Amount and total volume of glacial mudflows per year were used as indicators of the mudflow activity. 481 mudflows were recorded over 120 years of observations in the Zailiyskiy Alatau, and 24% of them were glacial mudflows. Glacial mudflows are the largest and most destructive. Of the nine mudflows with a volume of more than 1 million m3, seven were glacial mudflows. The chronicle of mudflow disasters is shown. From 1950 to 2019, 87 glacial mudflows were observed in the Zailiyskiy Alatau. Of these, 16 mudflows had volumes exceeding 100 thousand m3. The largest ones occurred in 1977 (6.0 million m3), 1963 (5.8 million m3), 1958 (4.0 million m3), and 1973 (3.8 million m3 ). The causes for formation of glacial mudflows are outbursts of moraine lakes or water from underground reservoirs, as well as collapses of moraines’ slopes. The largest of them occur when a lake is bursting through an open channel. Since 1951, occurrence of glacial mudflows has been increasing and reached its maximum in the 1970s. Since 1978, the number of glacial mudflows has been decreasing, although their volumes remained large until the late 1990s. From 1997 to 2013, mudflow activity was low. During 11 of the 15 years, no mudflow was observed. Every year only one mudflow happened with a volume below 10 thousand m3. Since 2014, there has been a tendency for an increase in mudflow activity. Large glacial mudflows were recorded in 2014 and 2019. To protect against mudflows in the valleys of the Zailiysky Alatau, 14 dams have been built and two more are planned. To prevent outbursts of moraine lakes, they are emptied using pumps and siphons. In 2019, the network of automated monitoring of early warning about mudflows is being organized, which will cover all the valleys of the Northern slope of the Zailiysky Alatau.